Peranan Koperasi Syariah dalam Mengatasi Kemiskinan di Kota Surabaya - Nur Aini Yandana Anggi Merisa Putri (Maliyah : Jurnal Hukum Bisnis Islam, 2018)
This article discusses sharia cooperatives and their role in overcoming poverty in the city of Surabaya. The city of Surabaya is the capital of the province of East Java, the largest and most populous city in East Java. Poverty is a problem that the city government of Surabaya always looks for a solution to. Various programs have been made, including through training, improvement of cooperatives, including Sharia cooperatives. This article is the result of a literature review and is qualitative in nature. The data collected through the literature were analyzed descriptively. The results of the study concluded that the Surabaya government made programs to alleviate poverty, including developing sharia cooperatives. With the existence of Islamic cooperatives, people can manage their funds and develop their businesses through Islamic cooperatives. Even though poverty cannot be eradicated, this effort is one way that can help prosper the community and help overcome existing poverty.